Slice area assessment of the gut-associated lymphoid tissue of sacculus rotundus in Hiplus rabbits - Slice area assessment of the gut-associated lymphoid tissue of sacculus rotundus in Hiplus rabbits (Bulgarian Journal of Veterinary Medicine, 2022)
The development of rabbit breeding requires research in various fields to ensure a high-grade product. One of the most important areas is the study of gut-associated lymphoid tissue. For the study, sacculus rotundus samples of clinically healthy rabbits of 1, 10, 20, 30, 60 and 90 days of age were collected. Microslide pictures were taken from the obtained intestine material. From the photos of the microslides, the characteristics of the slice area of aggregated lymphatic nodules, germinal centres and interfollicular regions were studied. The results can be used as indicators of the normal condition of healthy rabbits from the Hyplus meat breed.